Enhancing English Language Teaching through Teacher Professional Development - Saud, Dammar Singh (Far Western Review, 2025)
Enhancing English Language Teaching (ELT) requires well-designed and contextually relevant professional development (PD) for teachers, particularly in developing countries like Nepal. This paper explores the enhancement of English Language Teaching through teacher professional development, drawing upon Self Determination Theory and Socio cultural Theory as foundational frameworks. It critically reviews theoretical perspectives and recent empirical studies, including those focused on the Nepali ELT context. The paper identifies key characteristics of effective professional development, such as sustained engagement, collaborative inquiry, classroom applicability, and blended learning models. It also examines significant barriers to effective PD, including limited teacher motivation, inadequate resources, and structural or institutional constraints. Special attention is given to the realities of the Nepali education system, offering contextually grounded insights for policymakers, teacher educators, and school leaders. These insights emphasize fostering teacher autonomy, competence, and a sense of professional community to enhance both teaching quality and learner outcomes. By synthesising global best practices with local needs, this paper contributes to a deeper understanding of how evidence-based PD initiatives can improve ELT in resource constrained and culturally diverse settings like Nepal.